PENGARUH NON PERFORMING FINANCE (NPF), CAPITAL ADEQUACY RATIO (CAR) DAN OPERATIONAL EFFICIENCY RATIO (BOPO) TERHADAP FINANCIAL SUSTAINABILITY RATIO BANK UMUM SYARIAH TERDAFTAR DI OJK - Putri, Lodia Dwika; Nurmansyah, Nurmansyah; Tria Putri, Librina (Komunitas Manajemen Kompetitif, 2024)
This study aims to determine whether the effect of net performing financial (NPF), capital adequacy ratio (CAR) and operational efficiency ratio (BOPO) on financial sustainability ratio (FSR) at Indonesian Syariah Commercial Banks registered with the Financial Services Authority (OJK). 2018-2020. The population in this study at the same time used as a sample, amounting to 14 Indonesian Islamic banking companies. Processing and data analysis using multiple linear regression analysis with the SPSS program. The data test used for multiple linear regression is the classical assumption and hypothesis testing. The results of this study prove that partially the net performing financial (NPF) has a positive and significant effect on financial sustainability ratio (FSR), the capital adequacy ratio (CAR) has a negative and significant effect on financial sustainability ratio (FSR) and operational efficiency ratio (BOPO) has a negative and significant effect on financial sustainability ratio (FSR). Simultaneously, it proved that net performing finance (NPF), capital adequacy ratio (CAR) and operational efficiency ratio (BOPO) had a significant effect on financial sustainability ratio (FSR), with a significant value of 0.000 <0.05. The Adjusted R Square value shows a result of 0.987, which means that 98,7% financial sustainability ratio (FSR) is influenced by net performing financial (NPF), capital adequacy ratio (CAR) and operational efficiency ratio (BOPO). While the remaining 1,3% is influenced by other variables outside of this study. Keywords: Net Performing Financial (NPF), Capital Adequacy Ratio (CAR) and Operational Efficiency Ratio (BOPO) to Financial Sustainability Ratio (FSR)